الأسس لإعداد وتأليف مواد تعليم اللغة العربية - Falahun Ni'am (Imtiyaz : Jurnal Pendidikan dan Bahasa Arab, 2019)
The basics for preparing teaching materials are very important. The very first thing to consider when you are planning a learning experience is what exactly you intend your students to learn. Onsider the approach you would like students to take to their learning in your subject (The way in which you intend student to learn will, in many respects, dictate how you teach). Plan to evaluate your teaching and the subject regularly. Regular evaluation will enable you to improve the quality of the course and your teaching. This can be done by keeping a journal of activities and changes you would like to make (and the reasons for them!), by having other teachers 'sit in' on some classes, by asking the students what they have understood to be most important in each session, by having a focus group of students discuss important teaching and learning issues, and by using the Student Feedback Survey system.